Perception and Satisfaction of Orthodontic patients towards Orthodontic treatment in KIST Medical College and Teaching Hospital - Shrestha, Rosha; Acharya, Gaurav; Maskey, Suvit (Journal of Chitwan Medical College, 2025)
Introduction: Dental malalignment and aesthetics can negatively affect the patients’ psychology. This study aims to assess the perception and satisfaction of orthodontic patients at KIST Medical College and Teaching Hospital. Method: A cross-sectional survey was conducted after ethical approval among patients visiting the Orthodontics Department from 01 Jun to 01 Jul 2022 at KIST Medical College, Nepal. Patients undergoing fixed orthodontic treatment, aged ≥16 years, who consented were included. Patients with craniofacial deformities and cleft lip, palate were excluded. Data were collected using a structured questionnaire and consecutive sampling. Analysis was done in SPSS v16, for descriptive statistics and the Pearson chi-square test for association, with significance set at p≤0.05 Result: Out of 25 patients, majority160(64%) were females, and most of them (48%) aged 16-20 years. Females were more likely to wait for the next appointment (45%) than males (35.6%), and more males responded to social media (31.3%) than females (1.3%), p<0.05. Males (44.4%) sought treatment for bite correction, and females (38.8%) for appearance, p=0.022. More males (71.1%) were satisfied with dentofacial improvement than females (36.3%) (p=0.027). More females (53.3%) were willing to undergo treatment again than males (41.3%), p=0.037. Significant gender differences were observed in the perception of treatment as painful and the cost. Conclusion: We found that main reasons for orthodontic treatment were bite correction, improvement in appearance. Most perceive orthodontic treatment as a painful procedure. Most patients were pleased and satisfied with their treating doctor.